ARCHITECTURAL INTROSPECTION OF ISFAHAN JAME MOSQUE IN ADAPTION TO THE UNSEEN CONCEPTS OF PERSIAN LYRICS (10-12th SHAMSI) - Mohammadi, Fatimah Jalilzadeh; Adibzadeh, Bahman; Aminpour, Ahmad; Razjevian, Mahmoud (Journal of Islamic Architecture, 2020)
The language of paraphrase (taaâ€™wil, In Arabic: ØªØ§ÙˆÛŒÙ„ ) uses divine unseen (gheiybi, ØºÛŒØ¨) signs to shape the mosque institution. There are mosques and praying rituals for all realms: Literal (Mulki, Ù…ÙÙ„Ú©ÛŒ), Ethereal (Mithaali, Ù…Ø«Ø§Ù„ÛŒ), and Spiritual (Malakuti, Ù…Ù„Ú©ÙˆØªÛŒ). The rituals accomplish in mosque architecture in the hierarchy of being. The authority helps to explain the unseen concepts by paraphrase. The research questions are what factors have led to the manifestation of hidden ideas in the architecture of the Isfahan Jame Mosque objectively? And what are the evidence of unseen confirmations which led to introspection and personal approach? This research aims to answer the questions raised, then used a qualitative research method and describes the case study by using an analytical-introspective survey in combination with grounded theory to elucidate unseen concepts as esoteric meanings of architecture, in place and time. Numerous issues of the invisible architecture of mosque explain how to convert this mosque to desirable ones in the future.Â  The architecture of the Jame Mosque of Isfahan is a live example of unseen architecture. It has a close relationship with esoteric literature of not only its era but also for all periods of history. Issues of the invisible architecture of the mosque explain how to convert this mosque to desirable ones in the future.Â